An Assessment on the Test Anxiety and Academic Performance of Information Technology Students - Cochanco, Rose Anne G.; Olipas, Cris Norman P.; Cochanco, Alexander S.; Sison, Rosalie B. (International Journal of Advanced Engineering Research and Science, 2021)
In humans' daily life, people experience different levels of anxiety. Some experiences a low level of anxiety, others experience incredibly high. Anxiety significantly affects people in different forms. Higher education students experience anxiety attributed to different factors and one of which includes test anxiety. This study sought to describe the test anxiety among the Information Technology (IT) students and assess if test anxiety has a significant relationship to students' academic performance. The researchers applied a descriptive-correlational design to describe the IT students' test anxiety and test the relationship of the variables under investigation. The researchers adopted an instrument for this study. This study was conducted in a State University in Nueva Ecija, Philippines. A total of 394 students enrolled in an IT Major Course during the second semester of the academic year 2019-2020 voluntarily participated as respondents for this study. Results revealed that IT students have "somewhat typically" experienced test anxiety (WM = 2.734). Moreover, results showed that test anxiety among IT students has a significant positive relationship to their academic performance (p-value = 0.000, r = 0.347). Researchers suggest utilizing the positive effect of test anxiety in learning IT courses in order for students to improve their academic performance continuously.